COGNITIVE STUDY OF DEICTIC UNITS IN DIFFERENT STRUCTURAL LANGUAGES (Academicia Globe: Inderscience Research, 2022)
This article deals with the analysis of the role of deictic units in linguistics and the importance of deictic units in different systematic languages, the integral relationship of cognitive linguistics with deictic units and their characteristics.